CLINIC-EPYDEMIOLOGICAL PARTICULARITES OF B-CELL CHRONIC LYMPHOCYTIC LEUKOSIS IN THE KYIV REGION - Мельник, Ульяна; Выдыборец, Станислав (SWorldJournal, 2023)
The aim of this research was study of clinico-epidemiological peculiarities of the B-cell Chronic Lymphocytic Leukemia (B-CLL) in the Kyiv Region. 218 patients with CLL in the Clinical Hospital in the Institute of Hematology and Transfusiology of the NAMS